Proses Transformasi Digital pada Perguruan Tinggi di Indonesia - Andi Kambau, Ridwan (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
This research focuses on the challenges, strategies, and implementation of digital transformation in Indonesian higher education. Even though digital transformation in higher education is significant, Indonesia's geographic and demographic conditions cause different challenges in the West and East regions of the country. According to this research, digital transformation can improve operational efficiency, education quality, and student readiness for the digital era and Industry 4.0. Although there are similarities with developed countries, this research focuses on specific challenges such as equitable distribution of digital infrastructure, availability of human resources, and government support.This research uses a qualitative methodology and interpretive analysis. This research involved interviews and surveys of fifty academics from various regions in Indonesia. The results show that many areas have different ways of implementing digital transformation. This research also found the need for digital technology infrastructure, smart campus management, project-based learning approaches, and the availability of technology and human resource competencies, which are the main challenges.It was agreed that digital transformation must enter the fields of research and community service. Continuous evaluation, competency improvement, and redesign of educational programs are part of the implementation approach. The research results show different things about the situation in Indonesia. They also give colleges ideas about the best planning and implementation of digital transformation. The result is that this research emphasizes the differences and similarities in the digital transformation of higher education in Indonesia and provides a unique perspective on implementation challenges and strategies. This research can help universities develop digital transformation plans that suit Indonesia's exceptional circumstances.